2015
DOI: 10.1037/xhp0000095
|View full text |Cite
|
Sign up to set email alerts
|

When less is more: Impact of face processing ability on recognition of visually degraded faces.

Abstract: It is generally thought that faces are perceived as indissociable wholes. As a result, many assume that hiding large portions of the face by the addition of noise or by masking limits or qualitatively alters natural "expert" face processing by forcing observers to use atypical processing mechanisms. We addressed this question by measuring face processing abilities with whole faces and with Bubbles (Gosselin & Schyns, 2001), an extreme masking method thought by some to bias the observers toward the use of atypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 37 publications
5
38
1
Order By: Relevance
“…This indicates that more practice, t(19) ¼ 7.17, p , 0.001, 95% CI [2.87, 5.23], and more visual information, t(19) ¼ 15.07, p , 0.001, 95% CI [25.5, 33.7], were needed with spontaneous than with posed expressions to achieve a comparable accuracy rate. Indeed, it has recently been shown that the number of bubbles strongly correlates with the performance obtained with unaltered whole-face face stimuli (Royer, Blais, Gosselin, Duncan, Fiset, 2015). Mean accuracy rates for each expression are reported in Table 1.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This indicates that more practice, t(19) ¼ 7.17, p , 0.001, 95% CI [2.87, 5.23], and more visual information, t(19) ¼ 15.07, p , 0.001, 95% CI [25.5, 33.7], were needed with spontaneous than with posed expressions to achieve a comparable accuracy rate. Indeed, it has recently been shown that the number of bubbles strongly correlates with the performance obtained with unaltered whole-face face stimuli (Royer, Blais, Gosselin, Duncan, Fiset, 2015). Mean accuracy rates for each expression are reported in Table 1.…”
Section: Resultsmentioning
confidence: 94%
“…The results of that study were highly consistent with previous studies in which each face identity was presented hundreds of times-namely, the eye region was revealed as the most diagnostic for face identification. Relatedly, another study (Royer et al, 2015) compared the performance of participants in a task with the Bubbles method with their performance in tasks with unaltered faces (e.g., Cambridge Face Memory Test). It was shown that the correlation increased as a function of the number of trials performed in the task with the Bubbles method, suggesting that the overlap between the mechanisms involved in the Bubbles task and the ''normal'' faceprocessing mechanisms actually increased as a function of exposure to the task.…”
Section: Limits Of the Present Studymentioning
confidence: 99%
“…cropped to an elliptical shape). This objective was addressed using SF Bubbles, a variant of the Bubbles method (Gosselin & Schyns, 2001;Tadros, Dupuis-Roy, Fiset, Arguin & Gosselin, 2013;Royer, Blais, Gosselin, Duncan, & Fiset, 2015;Thurman, & Grossman, 2011;Willenbockel et al, 2010a;Willenbockel, Lepore, Bacon, & Gosselin, 2013;Willenbockel, Lepore, Nguyen, Bouthillier, & Gosselin, 2012). The basic idea behind SF Bubbles is that by randomly sampling certain SFs on a trial-by-trial basis, we will be able to pinpoint, after many trials, which SFs are significantly correlated with accuracy for identifying upright and inverted faces.…”
Section: Methodsmentioning
confidence: 99%
“…Another approach would be to use a measure of face recognition or inversion effects to validate the VHPT-F. But, recent evidence suggests that while holistic processing is routinely observed for faces but not objects in novices (e.g., Farah et al, 1998; Richler et al, 2011c), it does not relate to face recognition performance (Richler et al, 2015), which is instead predicted by performance with parts (Royer et al, 2015; Sunday et al, in submission), and whether upright and inverted faces rely on qualitatively different mechanisms is debated (e.g., Rossion and Boremanse, 2008 vs. Richler et al, 2011c). Indeed, trying to find a way to validate the VHPT-F reveals how little, we truly know about holistic processing, but it is exactly these kinds of questions that motivated us to pursue creation of reliable measures in the first place.…”
Section: Discussionmentioning
confidence: 99%